ANALISIS KECELAKAAN BUS RAPID TRANSIT (BRT) SEMARANG KORIDOR II TERMINAL TERBOYO – TERMINAL SISEMUT UNGARAN TAHUN 2016 - Dharurendra Negara; Siswi Jayanti; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
BRT Corridor II is a public transport serving passengers with Terminal Terboyo - Terminal Sisemut. There are eighteen cases of road accidents on BRT Corridor II in 2016. This study was conducted to analyze the cause of work accidents on roads and programs that have been done to reduce road accidents on BRT Corridor II driver. This type of research is descriptive research which is qualitative with in-depth interview and observation. Informants of this research are 2 drivers who have had an accident, 2 drivers who did not have an accident and operational officers. The results of this study indicate that there are 4 causes of work accidents on the road on BRT Corridor II driver in 2016 that are personal factors, job factors, substandard action, and substandard condition. Personal factors in question were long working hours and rest less, Job factors in question were the exceeds the limit of passenger charge. Substandard action in question were the lack of vigilance of the driver when driving that caused the collision, and other rider factors that hit the BRT. As for substandard condition in question were a vehicle inspection before driving less thorough and solid environment of the vehicle. The programs that had been implemented were new drivers' acceptance through complete requirements, meetings and briefing for drivers. Suggestions for the company are making a policy on K3, conducting scale health checks on workers, and evaluating the increase of passengers. While for workers is obeying work procedures and traffic regulations, conducting vehicle inspections correctly, and performing the passenger loading properly.